2020
DOI: 10.36899/japs.2020.2.0051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid and/or Alpha-Tocopherol Fortification on Semen Quality, Metabolic Profile, Antioxidants Status, and Dna of Roosters Exposed to Heat Stress

Abstract: This study investigates the influence of heat stress (HS) and vitamin C (VC) and/or vitamin E (VE) on semen quality, biochemical constituents of seminal and blood plasma, antioxidant status and jejunum and ilium deoxyribonucleic acid (DNA) of roosters. Forty-five, 32-week-old roosters were divided into five groups of nine replicates. One group was kept under a thermoneutral environment, whereas the other four were kept under HS. One of the four groups served as an unsupplemented HS group and was fed the basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…This observation agrees with the findings of Emadi et al (48) who report that the supplementation of L-Arg had no effect on total protein but significantly increased the albumin concentration in blood plasma. Attia et al (49) report that heat stress negatively affected chicken immune status by decreasing the blood plasma protein, γ-globulin (innate immunity), and blood plasma albumin (non-specific immune protein), which was recovered by supplementation with Vit E alone or with a combination of Vit C. In the present study, greater levels of plasma albumin in broilers fed the combination of PO and SO blend + 0.25% L-Arg + Vit E might be due to the greater body weight of broiler chickens in these groups, which had a higher concentration of plasma protein compared to lighter broilers in the control group; this suggests an increased demand for maintaining lean tissue growth. A synergistic effect of PO and SO blend, L-Arg, and Vit E was observed in blood plasma albumin (non-specific immune-protein), meat crude protein content, serum IgG and IgM level, and Vit E concentrations of meat, which could explain the superior performance of broilers in these treatment groups.…”
Section: Plasma Total Protein and Albumin Concentrationsmentioning
confidence: 99%
“…This observation agrees with the findings of Emadi et al (48) who report that the supplementation of L-Arg had no effect on total protein but significantly increased the albumin concentration in blood plasma. Attia et al (49) report that heat stress negatively affected chicken immune status by decreasing the blood plasma protein, γ-globulin (innate immunity), and blood plasma albumin (non-specific immune protein), which was recovered by supplementation with Vit E alone or with a combination of Vit C. In the present study, greater levels of plasma albumin in broilers fed the combination of PO and SO blend + 0.25% L-Arg + Vit E might be due to the greater body weight of broiler chickens in these groups, which had a higher concentration of plasma protein compared to lighter broilers in the control group; this suggests an increased demand for maintaining lean tissue growth. A synergistic effect of PO and SO blend, L-Arg, and Vit E was observed in blood plasma albumin (non-specific immune-protein), meat crude protein content, serum IgG and IgM level, and Vit E concentrations of meat, which could explain the superior performance of broilers in these treatment groups.…”
Section: Plasma Total Protein and Albumin Concentrationsmentioning
confidence: 99%
“…α-tocopherol (Vit E) is a chief lipid-soluble compound, which has a potent role as an antioxidant agent in vitro and in vivo research to protect cells against ROS (Rush et al, 2014;Attia et al, 2017;2020a). Several experiments indicated that the incorporation of α-tocopherol into embryo culture media improved the bovine and porcine blastocyst quality and embryo development (Natarajan et al, 2010;Olson and Seidel Jr, 2000).…”
Section: Vitamin Ementioning
confidence: 99%
“…Accumulating evidence indicates that ascorbic acid plays a vital role in several biological processes, specifically maintenance of redox status in different biological systems . It can decrease ROS by acting as a powerful antioxidant (non-enzymatic function), and as a crucial cofactor to regulate the family of ferrous ions and 2-oxoglutarate (Fe2+ and 2-OG)-dependent dioxygenases (enzymatic function) (Camarena and Wang, 2016;D'Aniello et al, 2017;Attia et al, 2020a). In pig oocytes, Vit C can reprogram the methylation status of not only DNA and histones, but also RNA (Yu et al, 2018).…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%